Analysis of NH3 emission characteristics from three–way catalyst cars. (4th August 2014) - Hori, S.; Sato, T.; Abe, T.
From the viewpoint of environmental protection, it has become important to estimate the emission of unregulated material from vehicles and to develop countermeasures which minimise these emissions. Ammonia is one such unregulated material which is emitted from three–way catalyst–equipped passenger cars. Thus, as described in this article, analyses of NH3 emission characteristics were carried out. Through engine and chassis dynamometer tests, the relationship between engine operating conditions and NH3 emission characteristics, as well as the influences of the air–fuel ratio control performance on NH3 emissions, were clarified.